Ethnocultural Contacts of the Peoples of the Altai-Sayan and Western Mongolia - Sampildondov, Chuluun; Dongak, Antonina S. (The New Research of Tuva, 2015)
Ethnocultural Contacts of the Peoples of the Altai-Sayan and Western Mongolia